FOUNDATIONAL APPROACH TO THE POLITICAL LANGUAGE OF THE COALITION OF PARTIES FOR DEMOCRACY IN CHILE. ANALYSIS OF THE CONCEPT OF DEMO - CRACY AND SOCIALISM IN POLITICAL JOURNALS DURING THE SECOND HALF OF 1980: THE CASE OF RICARDO LAGOS. - Kantar Contreras, Mauricio (Revista de Historia Social y de las Mentalidades, 2024)
The coup of 1973 opened in the Chilean left, particularly the Socialist Party and the MAPU, a process of self-criticism against the developments during the Popular Unity (UP), because this process rethinks and redefines fundamental concepts of theoretical heritage left by changing the political language of opposition to dictatorship. In this scenario, we reviewed the adequacies, conceptual elaborations and applications of democracy and socialism, the Socialist leader Ricardo Lagos developed from the platform of opposition political magazines to the dictatorial regime.